Discretized Impedance-Based Modeling of Converter-Interfaced Energy Resources for State-Variable-Based Real-Time EMT Simulators - Taleb Vahabzadeh; Seyyedmilad Ebrahimi; Juri Jatskevich (IEEE Open Journal of Power Electronics)
Modern power systems are experiencing high penetration of voltage-source converter (VSC)-interfaced distributed energy resources and loads. Design, analysis, and reliable operation of such systems require extensive offline and real-time electromagnetic transient (EMT) simulations. This paper proposes discretized impedance-based modeling (DIBM) of VSCs for efficient time-domain transient analysis in state-variable (SV)-based EMT simulators. Specifically, the VSC-based systems are first represented as admittance-based models in Laplace domain, and then they are discretized and formulated to construct a Thévenin equivalent impedance matrix and history voltages that can be interfaced seamlessly with external systems in SV-based simulators. By replacing VSC subsystems with Thévenin equivalent circuits, the proposed DIBM technique significantly reduces the number of states and eliminates the need for fictitious snubbers that may be needed in SV-based EMT simulators for compatible interfacing. The effectiveness of the proposed DIBM approach over the conventional method that uses average value models of VSCs is demonstrated on a seven-bus VSC-based system in offline (MATLAB Simscape Electrical) and real-time (OPAL-RT) EMT simulators. It is verified that the proposed method enables high accuracy and larger simulation time steps while also significantly improving the overall computational performance.